Linguistic and communicational analysis on public opinion in Eurobarometer 2010-2012 - Kovtyk, Bogdan (Glottodidactica, 2014)
The article is dealing with aspects of European communication based on Eurobarometer 2010-2012 exploring the evolution of the public opinion of the EU Member States. The analysis of the European communication will be realized by linguistic and communication research tools such as semiotic-mythological method, discursive method, socio-psychological method, semantic differential, contrastive method and questionnaires. The general aim of the article is concentrated on the research of interconnected impacts of public opinions along central European questions and in comparison between opinion items in Poland and Germany.